2019
DOI: 10.1080/09638288.2019.1568592
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of patients managed in specialist versus non-specialist inpatient rehabilitation units in Australia

Abstract: A comparison of patients managed in specialist versus non-specialist A comparison of patients managed in specialist versus non-specialist inpatient A comparison of patients managed in specialist versus non-specialist inpatient rehabilitation units in Australia rehabilitation units in Australia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…These differences would suggest that a patient's dysphagia rehabilitation is optimized in a specialist center with access to a specialist dysphagia team including a Speech-Language Pathologist (SLP). There is an indication that those receiving rehabilitation in a specialist center achieve greater functional gains than those who do not [137]. This is supported by McRae's findings [136] that non-specialist centers had lower expectations for patients returning to safe eating and drinking and an increased reliance on diet and fluid modifications to manage dysphagia.…”
Section: Implications For Clinical Practicementioning
confidence: 89%
“…These differences would suggest that a patient's dysphagia rehabilitation is optimized in a specialist center with access to a specialist dysphagia team including a Speech-Language Pathologist (SLP). There is an indication that those receiving rehabilitation in a specialist center achieve greater functional gains than those who do not [137]. This is supported by McRae's findings [136] that non-specialist centers had lower expectations for patients returning to safe eating and drinking and an increased reliance on diet and fluid modifications to manage dysphagia.…”
Section: Implications For Clinical Practicementioning
confidence: 89%
“…Highlighting the importance of high quality inpatient ABI rehabilitation ("Rehabilitation of persons with traumatic brain injury," 1998), it has been shown that early functional gains can be made by people with ABI who receive intensive programmes delivered by experienced, multidisciplinary teams early in their recovery (Turner-Stokes et al, 2015). Further, receiving such programmes in a specialised brain injury rehabilitation unit can lead to greater functional gains than for people in non-specialised facilities (McKechnie, Pryor, Fisher & Alexander, 2020).…”
Section: Introductionmentioning
confidence: 99%